Méta-theologie analytique - Alejandro Pérez (Scientia et Fides, 2018)
Analytic meta-theology What is analytic theology? How should we go about doing analytic theology and what can we expect from? These questions seem to be today´s challenge for analytic theology. These questions will be answered by distinguishing analytic theology from other disciplines with which it seems to be confused. We will propose a new definition of analytic theology based on three criteria, and examining two ways of doing analytic theology: (i) a bottom up and (ii) a top down approach. According to our thesis, only a confessing top down analytic theology can be considered as analytic theological theology.